PEMBINGKAIAN PEMBERITAAN PENYERANGAN KELOMPOK INTOLERAN PADA ACARA MIDODARENI DI SOLO: (Analisis Framing cnnindonesia.com dan kompas.com Periode 10 Agustus-21 September 2020) - lina amiliya (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2021)
Online media into the media to convey information to the public. Speed ​​in conveying news faster makes it a distinct advantage. An example of the attack on an intolerant group at the Midodareni event in Solo. This incident adds to the bad record of intolerance in Indonesia, which should uphold the values ​​of diversity. In fact, this incident aroused empathy and angered many parties, such as Governor Ganjar Pranowo, Alissa Wahid, the first daughter of the 4th President of the Republic of Indonesia KH Abdurrahman Wahid, Minister of Religion Fachrul Razi and Komnas HAM. In this event, such as cnnindonesia.com and kompas.com as media online international and national which also published news about the attack on intolerant groups at the Midodareni event in Solo. In this study, the researcher used the analysis method of framing the Zhongdang Pan and Gerald M Kosicki model with 4 structural dimensions of the news text as adevice, framing namely syntax, script, thematic and rhetorical. This method is used to see how a media constructs reality, and how events are understood and framed by the media. As a result, cnnindonesia.com and kompas.com when reporting on the case by emphasizing several aspects, namely the selection of news sources such as authorities, quotes from news sources, news completeness standards, statements or opinions, and images used to support the structure framing.